2014
DOI: 10.1287/orsc.2013.0878
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Competition as a Double-Edged Sword: How Sex Composition Regulates the Effects of Competition on Group Creativity

Abstract: Building on social role theory, we extend a contingency perspective on intergroup competition proposing that having groups compete against one another is stimulating to the creativity of groups composed largely or exclusively of men but detrimental to the creativity of groups composed largely or exclusively of women. We tested this idea in two separate studies: a laboratory experiment (Study 1) and a field study (Study 2). Study 1 showed that competition had the expected positive effects on the creativity of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 74 publications
(86 reference statements)
3
27
0
4
Order By: Relevance
“…From a theoretical perspective, gender diversity increases creativity and innovation, as it leads to a greater diversity in terms of skills and abilities (Lazear, 1999;Baer et al, 2013). This argument is in line with Cumming and Oldham (1997), and with Bharadwaj and Menon (2000), who point out that team creativity is crucial for innovation at company level.…”
Section: Gender Diversity and Innovationsupporting
confidence: 58%
“…From a theoretical perspective, gender diversity increases creativity and innovation, as it leads to a greater diversity in terms of skills and abilities (Lazear, 1999;Baer et al, 2013). This argument is in line with Cumming and Oldham (1997), and with Bharadwaj and Menon (2000), who point out that team creativity is crucial for innovation at company level.…”
Section: Gender Diversity and Innovationsupporting
confidence: 58%
“…Experimental studies of groups of undergraduates and scientists in the real world have revealed important differences between how men and women tend to respond to competition. In one such study, intense competition between teams enhanced creativity in teams composed of men but impeded creativity in teams composed of women, whereas women thrived in a collaborative environment in which teams worked side by side (54). This might relate to deep-seated gender differences in cooperation and competition that have been designated the "male-warrior hypothesis" (55).…”
mentioning
confidence: 99%
“…Baer et al (2013) find a positive effect of competition on creativity. Another aspect influenced by competition is that more "experimentation" and "creative destruction" take place.…”
Section: Walking Parallel Paths or Taking The Same Road?mentioning
confidence: 84%